(Co, Mn)-Doped NiSe2-diethylenetriamine (dien) nanosheets and (Co, Mn, Sn)-doped NiSe2 nanowires for high performance supercapacitors: compositional/morphological evolution and (Co, Mn)-induced electron transfer. Issue 36 (30th August 2019) - Dan, Huamei; Tao, Keyu; Hai, Yang; Liu, Li; Gong, Yun
Abstract : A series of MSe2 -dien (M = metal(ii ) ion and dien = diethylenetriamine) were grown on Ni foam (NF) based on Co(ii )/Mn(ii ) salts with different molar ratios. Abstract : A series of MSe2 -dien (M = metal(ii ) ion and dien = diethylenetriamine) were grown on Ni foam (NF) based on Co(ii )/Mn(ii ) salts with different molar ratios. It was found that the Co-free sample exhibited hollow tubes built by numerous interconnected nanowires, whereas nanosheets were observed in the Co-involved samples. The formation of nanosheets is associated with Co(ii ), which is due to the fact that Co(ii ) promotes the metal selenide nanosheet to grow along its (011̄) facet (thickness direction). Furthermore, the formation and compositional/morphological evolution of the samples were investigated. Among them, (Co, Mn)-NiSe2 -dien/NF (2 : 1-Co/Mn sample) showed the largest specific capacity of 288.6 mA h g −1 at 1 A g −1 with a retention of 69% at 10 A g −1 (198.6 mA h g −1 ), which is associated with its ultrathin nanosheet arrays and the co-doping of (Co, Mn) into NiSe2 -dien, leading to the redistribution of electron densities around the Ni and Se centers. XPS and density functional theory (DFT) calculations proved the electron transfer from NiSe2 -dien to the adsorbed OH − ions from the electrolyte solution, which can facilitate the redox reaction between active sites and electrolyte ions to enhance the electrochemical performance. A hybrid supercapacitor, (Co, Mn)-NiSe2 -dien/NF//activated carbon, was fabricated, which displayed an energy density of 50.9 W h kg −1 at a power density of 447.3 W kg −1 and good cycling stability with 84% capacity retention after 10 000 charge–discharge cycles. Furthermore, (Co, Mn)-doped NiSe2 -dien nanosheets could be transformed into (Co, Mn, Sn)-doped NiSe2 nanowire arrays after immersion in SnCl2 alcoholic solution due to cation exchange and the Kirkendall effect, and the obtained sample exhibited a decent areal capacity of 0.267 mA h cm −2 at 5 mA cm −2 .